Effects of exopolysaccharides from Antrodia cinnamomea on inflammation and intestinal microbiota disturbance induced by antibiotics in mice. (December 2022) - Lu, Chun-lei; Lee, Byong H.; Ren, Yi-lin; Ji, Dan; Rao, Sheng-qi; Li, Hua-xiang; Yang, Zhen-quan
Abstract: Antrodia cinnamomea is an important edible and medicinal mushroom, and it exhibits multiple biological activities, such as hepatoprotection, antitumor, antivirus, and immunoregulation. Polysaccharides are the main products of A. cinnamomea in submerged fermentation. In this work, exopolysaccharides from A. cinnamomea (AEPS) were extracted and purified by alcohol precipitation and Sevag method. Composition analysis revealed that AEPS were primarily composed of three distinct polysaccharides with mean molecular weights of 1, 013, 233, and 28, 743 kDa, accounting for 78%, 18%, and 4% of AEPS, respectively. The AEPS have β-type glycosidic bonds and relatively strong resistance to digestion. In vivo experiments showed that the intragastric administration of AEPS in mice with medium dose (0.25 g/kg body weight of mice) has the following effects: remarkably alleviate lincomycin hydrochloride (LIH)-induced injuries to immune organs; enhance the relative abundance of beneficial microorganisms such as Lactobacillus, Roseburia, Ligilactobacillus, and Lachnospiraceae _NK4A136_ group in the intestinal tract; greatly reduce the levels of inflammatory cytokines IL-6 and TNF-α in serum and the relative abundances of harmful microbes such as Enterococcus and Shigella ; regulate the balance of the gut microflora; and relieve LIH-induced symptoms such as diarrhea, inflammation, and weight loss. These findings might represent a new alternative to develop novel multifunctional carbohydrate prebiotics.